DNA Techniques in the register and protection of plant varieties rights - Ю. М. Сиволап; Н. Е. Кожухова (Plant Varieties Studying and Protection)
Modern state of DNA-markers introduction in world plant breeding practice was analyzed. Results of South plant biotechnology center research activity (Odessa), directed on DNA-technologies development for differentiation, identification and registration of important agricultural crops were given.